2009
DOI: 10.1007/s00269-009-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion and decomposition of jarosite: a high-temperature neutron diffraction study

Abstract: The structure of deuterated jarosite, KFe3(S04)2(OD)6, was investigated using time-of-flight neutron diffraction up to its dehydroxylation temperature. Rietveld analysis reveals that with increasing temperature, its c dimension expands at a rate ~10 times larger than that for a. This anisotropy of thermal expansion is due to rapid increase in the thickness of the (001) On heating, the hydrogen bonds, 01···D-03, through which the (001) octahedral tetrahedral sheets are held together, become weakened, as reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…However, they note that there is a transition into a long-range ordered antiferromagnetic state at 65 K, and associated structural relaxation may account for the discrepancy. Conversely, our 297 K data are in good agreement with the 298 K data from the powder neutron diffraction study of Xu et al (2010), and our plots of c and V against temperature (Figs. 2a and 2b) extrapolate into theirs for the range T = 298-575 K with only slight breaks in slope.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, they note that there is a transition into a long-range ordered antiferromagnetic state at 65 K, and associated structural relaxation may account for the discrepancy. Conversely, our 297 K data are in good agreement with the 298 K data from the powder neutron diffraction study of Xu et al (2010), and our plots of c and V against temperature (Figs. 2a and 2b) extrapolate into theirs for the range T = 298-575 K with only slight breaks in slope.…”
Section: Resultssupporting
confidence: 86%
“…2a and 2b) extrapolate into theirs for the range T = 298-575 K with only slight breaks in slope. Our a-axis at 297 K is also close to that of Xu et al (2010), however, our data do not lie on their trend for T ≥ 350 K of a increasing nonlinearly with T. The a-axis of Xu et al (2010) increases by only 0.09% over 350-575 K, while c increases an order of magnitude more (0.91%), so the extreme anisotropy in expansion is maintained to high temperatures. In combination, the data sets of Inami et al (2000), Xu et al (2010), and this study, suggest that the jarosite a-axis reaches a minimum value near 300 K, varies by only a small amount, but possibly in a complex fashion, over the temperature range of our study, and increases again below the magnetic transition at 65 K.…”
Section: Resultssupporting
confidence: 54%
“…The linear thermal expansion coefficients, determined in the temperature range 50À475ºC (lower and upper limits excluded in the calculation) by least-squares regression analysis, are a a = 0.61(2)610 À5 K À1 (R 2 = 0.988), a c = 4.20(7)610 À5 K À1 (R 2 = 0.996), ratio a c /a a = 6.89, a V = 5.45 (7) (2) Site Al, Wyckoff position 9d (0,1/2,1/2) Occ. Al 0.988(4) 0.975 (7) 0.972 (7) 0.963(6) 0.964 (7) 0.972 (7) 0.932(18) U 11 4(1) 4(1) 6(1) 7(1) 8(1) 9(1) 11(2) U 22 5(1) 6(1) 7(1) 9(1) 10(1) 11(1) 13(2) U 33 9(1) 10 (1) 12 (1) 14 (1) 17 (1) 19(1) 54(4) (1) 12 (1) 13 (1) 26 (2) Site S, Wyckoff position 6c (0,0,z) z/c 0.30282(4) 0.30257 (6) 0.30215 (7) 0.30179 (6) 0.30142 (7) 0.30118 (7) 0.3010(3) U 11 6(1) 8 (1) 10 (1) 12 (1) 14 (1) 16 (1) 19(1) U 33 7(1) 9(1) 9(1) 11 (1) 15 (1) 16 (1) 51(3) U 12 3(1) 4(1) 5(1) 6(1) 7(1) 7(1) 9(1) U eq 6(1) 8(1) 10 (1) 12 (1) 14 (1) coefficient along a is only slightly larger than jarosite, which has a a = 0.41610 À5 K À1 (Xu et al, 2010). Although the variations are very small, the data of Xu et al (2010) on the a cell parameter as a function of T in jarosite might be better interpreted using a T-dependent model or by hypothesizing a change in the slope at 150À175ºC.…”
Section: Results and Discussion Thermal Expansionmentioning
confidence: 96%
“…Al 0.988(4) 0.975 (7) 0.972 (7) 0.963(6) 0.964 (7) 0.972 (7) 0.932(18) U 11 4(1) 4(1) 6(1) 7(1) 8(1) 9(1) 11(2) U 22 5(1) 6(1) 7(1) 9(1) 10(1) 11(1) 13(2) U 33 9(1) 10 (1) 12 (1) 14 (1) 17 (1) 19(1) 54(4) (1) 12 (1) 13 (1) 26 (2) Site S, Wyckoff position 6c (0,0,z) z/c 0.30282(4) 0.30257 (6) 0.30215 (7) 0.30179 (6) 0.30142 (7) 0.30118 (7) 0.3010(3) U 11 6(1) 8 (1) 10 (1) 12 (1) 14 (1) 16 (1) 19(1) U 33 7(1) 9(1) 9(1) 11 (1) 15 (1) 16 (1) 51(3) U 12 3(1) 4(1) 5(1) 6(1) 7(1) 7(1) 9(1) U eq 6(1) 8(1) 10 (1) 12 (1) 14 (1) coefficient along a is only slightly larger than jarosite, which has a a = 0.41610 À5 K À1 (Xu et al, 2010). Although the variations are very small, the data of Xu et al (2010) on the a cell parameter as a function of T in jarosite might be better interpreted using a T-dependent model or by hypothesizing a change in the slope at 150À175ºC. The jarosite thermal expansion coefficient along a calculated for RTÀ175ºC is the same as for alunite, and this suggests that the particular trivalent octahedral cation in the R position has little effect on the thermal expansion behaviour of the structure.…”
Section: Results and Discussion Thermal Expansionmentioning
confidence: 96%
“…(6)) ( Baron and Palmer, 1996;Drouet and Navrotsky, 2003;Smith, 2004;Forray et al, 2005). However, both Frost et al (2005) and Xu et al (2010) have reported widely varying temperatures at which these weight loss stages occur depending on either composition or crystallinity.…”
Section: Introductionmentioning
confidence: 96%